Intergenerational transmission of post‐traumatic stress disorder in Australian Vietnam veterans' families. (28th December 2016) - O'Toole, B. I.; Burton, M. J.; Rothwell, A.; Outram, S.; Dadds, M.; Catts, S. V.
Abstract : Objective: To assess the association between parental post‐traumatic stress disorder (PTSD) and offspring PTSD and its specificity for other disorders in a non‐clinical epidemiological cohort of Australian Vietnam veterans, their partners and their sons and daughters. Method: Veterans were interviewed twice, in 1992–1994 and 2005–2006; partners were interviewed in 2006–2007, and their offspring in 2012–2014. A total of 125 sons and 168 daughters were interviewed from 197 families, 137 of which also included partners who were the mothers of the children. Statistical analysis used multi‐level modelling to compute odds ratios and 95% confidence intervals while controlling for clustering effects within families. Parent PTSD diagnoses were examined for associations with offspring trauma exposure, PTSD and other psychiatric diagnoses. Results: Veteran PTSD increased the risk of PTSD and no other disorder in both sons and daughters; partner PTSD did not. Veteran depression was also a risk factor for sons' PTSD, and alcohol disorder was linked to alcohol dependence in sons and PTSD in daughters, but not when controlling for veteran PTSD. Conclusion: We conclude that PTSD in a Vietnam veteran father increases the risk specifically for PTSD in his sons and daughters.